Sajjilu Arab American : a reader in SWANA studies - Cainkar, Louise; Vinson, Pauline Homsi; Jarmakani, Amira, 1974- (Critical Arab American studies., 2022)
"'Sajjulu Arab American' is a carefully curated multi-disciplinary collection of scholarly writings in Arab American studies. Written by both recognized and emerging scholars, the collected essays utilize a wide range of theoretical frames and analytic lenses that are essential to understanding the field"--